Subject-specific estimation of central aortic blood pressure via system identification: preliminary in-human experimental study - Fazeli, Nima; Kim, Chang-Sei; Rashedi, Mohammad; Chappell, Alyssa; Wang, Shaohua; MacArthur, Roderick; McMurtry, M. Sean; Finegan, Barry; Hahn, Jin-Oh (Medical & biological engineering & computing, 2014)
This paper demonstrates preliminary in-human validity of a novel subject-specific approach to estimation of central aortic blood pressure (CABP) from peripheral circulatory waveforms. In this “Individualized Transfer Function” (ITF) approach, CABP is estimated in two steps. First, the circulatory dynamics of the cardiovascular system are determined via model-based system identification, in which an arterial tree model is characterized based on the circulatory waveform signals measured at the body’s extremity locations. Second, CABP waveform is estimated by de-convolving peripheral circulatory waveforms from the arterial tree model. The validity of the ITF approach was demonstrated using experimental data collected from 13 cardiac surgery patients. Compared with the invasive peripheral blood pressure (BP) measurements, the ITF approach yielded significant reduction in errors associated with the estimation of CABP, including 1.9–2.6 mmHg (34–42 %) reduction in BP waveform errors ( p < 0.05) as well as 5.8–9.1 mmHg (67–76 %) and 6.0–9.7 mmHg (78–85 %) reductions in systolic and pulse pressure (SP and PP) errors ( p < 0.05). It also showed modest but significant improvement over the generalized transfer function approach, including 0.1 mmHg (2.6 %) reduction in BP waveform errors as well as 0.7 (20 %) and 5.0 mmHg (75 %) reductions in SP and PP errors ( p < 0.05).